Pablos Pons, J. De (coord.) (2015). Los centros educativos ante el desafío de las tecnologías digitales. Madrid: La Muralla - Revuelta Domínguez, Francisco Ignacio (Revista Fuentes, 2015)
Pablos Pons, J. De (coord.) (2015). Los centros educativos ante el desafío de las tecnologías digitales. Madrid: La Muralla